2022
DOI: 10.1186/s12891-022-05417-3
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the cervicothoracic junction during posterior cervical laminectomy and fusion for the treatment of multilevel cervical ossification of the posterior longitudinal ligament: a retrospective case series

Abstract: Background The purpose of this study was to investigate the surgical efficacy of crossing the cervicothoracic junction during posterior cervical laminectomy and fusion for the treatment of multilevel cervical ossification of the posterior longitudinal ligament (OPLL). Methods From October 2009 to October 2017, 46 consecutive patients with multilevel cervical OPLL underwent posterior cervical laminectomy and crossing the cervicothoracic junction fus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…OPLL was defined, as in other studies, as heterotopic ossification of more than 2 mm on the posterior side of the vertebral body 14,15 . Surgery was performed in patients where spinal cord compression caused by OPLL was confirmed on preoperative MRI and was associated with significant neurologic deficits.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…OPLL was defined, as in other studies, as heterotopic ossification of more than 2 mm on the posterior side of the vertebral body 14,15 . Surgery was performed in patients where spinal cord compression caused by OPLL was confirmed on preoperative MRI and was associated with significant neurologic deficits.…”
Section: Methodsmentioning
confidence: 99%
“…OPLL was defined, as in other studies, as heterotopic ossification of more than 2 mm on the posterior side of the vertebral body. 14,15 Surgery was performed in patients where spinal cord compression caused by OPLL was confirmed on preoperative MRI and was associated with significant neurologic deficits. Surgical segments included levels with cord compression, and the surgical approach was typically decided based on the extent of OPLL and patient symptoms.…”
mentioning
confidence: 99%
“…The systematic search yielded 1528 articles, of which 553 were duplicates, and 942 were excluded by screening the title and abstract. After a full-text review, 18 studies were considered improper: six for including patients with diagnosis of trauma, infection, or tumour [13,14,[24][25][26][27]; five for non-comparative study (cervical group vs. thoracic group) [9,[28][29][30][31]; three for the absence of necessary outcomes [12,32,33]; three for partly duplicated cohorts [11,34,35]; and one for non-English study [36]. Finally, 15 studies were included in this systematic review and meta-analysis (Figure 1) [37][38][39][40][41][42][43][44][45][46][47][48][49][50][51].…”
Section: Study Selectionmentioning
confidence: 99%
“…These unphysiological biomechanics increase the intradiscal pressures and motion of C7-T1, which would accelerate the degeneration of this level and induce adjacent segment disease (ASD) or other mechanical complications. Therefore, some studies have recommended prophylactic extension of the fusion construct into the upper thoracic spine, crossing the CTJ, to reduce the rate of complications and need for reoperations [9][10][11]. In contrast, some investigators reported that this procedure would further increase surgical invasiveness and disrupt the posterior stabilising structures, which have no benefits in solid fusion [12][13][14].…”
Section: Introductionmentioning
confidence: 99%